Volatile fatty acid production dynamics during the acidification of pretreated olive mill wastewater. (October 2017) - Yarimtepe, Canan Can; Oz, Nilgün Ayman; Ince, Orhan
Highlights: Acidification of olive mill wastewater was investigated at different loading rates. Dynamics of VFA production has been investigated. tVFA production and VFAs conversion were monitored for a cycle period (a day). A high VFA production was obtained at 20 g sCOD/L with 68% acidification rate. Possible alternative VFA recovery methods were discussed. Abstract: This study focuses on the dynamics of VFA production from pretreated olive mill wastewater (OMW). Acidogenic anaerobic sequencing batch reactors (AcASBR) were operated with the pretreated OMW at hydraulic retention time (HRT) of 2 days and pH of 5, 5 for different organic loading rates (OLRs) ranging from 5 g COD/L.d to 40 g COD/L.d. VFA production reached to the highest value of about 27, 000 mg/L with the increase in the organic load applied (20 g COD/L.d). The highest acidification rate was calculated as 68%. Acetic acid was found to be as the dominant VFA compound for all stage of the study. At steady state, VFA production during a day-cycle period (24th hour) in AcASBR is also monitored, VFA production gradually increased after the 3rd and 6th hours (about 20%) and a rapid increase (about 40%) was observed reaching the maximum at the end of the cycle (24th hour).